2017
DOI: 10.1002/jat.3475
|View full text |Cite
|
Sign up to set email alerts
|

Review of mechanisms of deoxynivalenol‐induced anorexia: The role of gut microbiota

Abstract: Deoxynivalenol (DON) is one of the most important mycotoxins in cereal-based foods or other food productions, produced by Fusarium species. Because of the high occurrence of DON in food combined with vast consumption of cereals and grain worldwide, the DON-contaminated food is a very harmful factor for human and animal health. DON has been reported to induce anorexia at lower or chronic doses in animal models. However, further researches for DON-induced anorexia are limited. Previous publications demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 60 publications
5
21
0
Order By: Relevance
“…DON significantly promoted the levels of GLP1, leptin, and insulin compared to the Con group in the present study, and GLP1 and leptin lead to reduced food intake [36,37]. 5-HT plays an important role in the DON-induced suppression of feed intake [28,38]. BCU downregulated the expression of HTR3A1 in the hypothalamus in no DON-treated piglets in the current study, and downregulated the expression of 5-HT in the hypothalamus in DON-treated piglets, which shows that BCU promoted piglets to eat normal feed and inhibited piglets from eating DON-contaminated feed.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…DON significantly promoted the levels of GLP1, leptin, and insulin compared to the Con group in the present study, and GLP1 and leptin lead to reduced food intake [36,37]. 5-HT plays an important role in the DON-induced suppression of feed intake [28,38]. BCU downregulated the expression of HTR3A1 in the hypothalamus in no DON-treated piglets in the current study, and downregulated the expression of 5-HT in the hypothalamus in DON-treated piglets, which shows that BCU promoted piglets to eat normal feed and inhibited piglets from eating DON-contaminated feed.…”
Section: Discussionsupporting
confidence: 56%
“…DON induces anorexia, growth retardation, and inflammatory responses in human and animals [1,3]. Abundant scientific evidence shows that DON leads to changes in the composition of the intestinal microbiota, stimulates the immune system, and induces the secretion of gut hormones, which act on the pituitary and hypothalamus via the brain-gut axis, resulting in decreased appetite and growth retardation in humans and animals [28]. The present study described the impacts of dietary BCU supplementation on the intestinal microbiota composition, inflammatory responses, and hormone secretion in DON-challenged piglets.…”
Section: Discussionmentioning
confidence: 99%
“…A study has found that the relative size of the two largest phyla of bacteria in the gut, Firmicutes and Bacteroidetes, differ amongst obese and lean individuals. Firmicutes levels have been found to be higher in obese individuals when compared to lean individuals [54]. Whereas Bacteroidetes have been observed to increase in numbers as one loses weight [55].…”
Section: Discussionmentioning
confidence: 99%
“…The intestinal flora not only participates in the processing of nutrients and regulates the formation of intestinal blood vessels, but also promotes the development of the GALT and mucosal immunity, induces immune tolerance, as well as produces a diverse spectrum of pre-immune antibodies [41]. The intestinal microbiome can act as a signal hub linking the immune system and intestinal microflora, and their abnormal communication may give rise to complex diseases [42,43].…”
Section: Don Intestinal Microbiota and Galtmentioning
confidence: 99%